2014
DOI: 10.1371/journal.pone.0090588
|View full text |Cite
|
Sign up to set email alerts
|

A Pepper MSRB2 Gene Confers Drought Tolerance in Rice through the Protection of Chloroplast-Targeted Genes

Abstract: BackgroundThe perturbation of the steady state of reactive oxygen species (ROS) due to biotic and abiotic stresses in a plant could lead to protein denaturation through the modification of amino acid residues, including the oxidation of methionine residues. Methionine sulfoxide reductases (MSRs) catalyze the reduction of methionine sulfoxide back to the methionine residue. To assess the role of this enzyme, we generated transgenic rice using a pepper CaMSRB2 gene under the control of the rice Rab21 (responsive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 63 publications
0
19
0
Order By: Relevance
“…The subcellular localization of some of them was proven experimentally, as reported for the three plastidial MSRA4, MSRB1, and MSRB2 isoforms [ 49 , 50 ], MSRB7 and MSRB8 in cytosol [ 51 ], and MSRB3 in endoplasmic reticulum [ 52 ]. Consistently, several MSRA and MSRB isoforms from other species (rice, tobacco, tomato, pepper, soybean, papaya, and banana) were found to localize in cytosol and plastids in Arabidopsis protoplasts using a bimolecular fluorescence complementation (BiFC) approach [ 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 ]. In other respects, data gained from BiFC experiments suggest that some cytosolic MSRA and MSRB isoforms from litchi and banana are present both in cytosol and in nucleus [ 61 , 62 ].…”
Section: Subcellular Localization and Organ Distribution Of Plant mentioning
confidence: 86%
See 2 more Smart Citations
“…The subcellular localization of some of them was proven experimentally, as reported for the three plastidial MSRA4, MSRB1, and MSRB2 isoforms [ 49 , 50 ], MSRB7 and MSRB8 in cytosol [ 51 ], and MSRB3 in endoplasmic reticulum [ 52 ]. Consistently, several MSRA and MSRB isoforms from other species (rice, tobacco, tomato, pepper, soybean, papaya, and banana) were found to localize in cytosol and plastids in Arabidopsis protoplasts using a bimolecular fluorescence complementation (BiFC) approach [ 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 ]. In other respects, data gained from BiFC experiments suggest that some cytosolic MSRA and MSRB isoforms from litchi and banana are present both in cytosol and in nucleus [ 61 , 62 ].…”
Section: Subcellular Localization and Organ Distribution Of Plant mentioning
confidence: 86%
“…Thus, in rice, overexpression of plastidial MSRA4.1 is associated with improved tolerance to high salt (300 mM NaCl), as inferred from photosynthetic activity and oxidative damage measurements [ 55 ]. Furthermore, rice plants overexpressing pepper MSRB2 exhibit better tolerance to water deficit than WT upon shortage and higher survival rate following re-watering [ 57 , 114 ]. In these plants, microarray analysis indicated that genes coding for photosystem components are much less down-regulated in drought conditions than in WT [ 57 ].…”
Section: Physiological Functions Of Plant Msrsmentioning
confidence: 99%
See 1 more Smart Citation
“…Agb0103 was a drought‐tolerant transgenic rice using a CaMSRB2 ( Capsicum annuum Methionine sulphoxide reductase B2) gene and bar (phosphinothricin acetyltransferase) gene with the Agrobacterium ‐mediated transformation (Kim et al ., ). The CaMSRB2 ‐overexpression transgenic rice has the tolerance to the drought treatment during vegetative stage.…”
Section: Methodsmentioning
confidence: 99%
“…CaMSRB2 gene was cloned into the pSB‐Rab21 without the potato protease inhibitor II terminator/35S promoter/bar, resulting in the plasmid MSRB2‐mini. Finally, the constructs were introduced into Agrobacterium tumefaciens LBA4404 by triparental mating (Kim et al ., ).…”
Section: Methodsmentioning
confidence: 99%